The - Wilde, Oscar (Chatterley Press International, 2006)
Since its first publication in 1890, Oscar Wilde's only novel, The Picture of Dorian Gray, has remained the subject of critical controversy. Acclaimed by some as an instructive moral tale, it has been denounced by others for its implicit immorality. After having his portrait painted, Dorian Gray is captivated by his own beauty. Tempted by his world-weary friend, decadent friend Lord Henry Wotton, he wished to stay young forever and pledges his very soul to keep his good looks. As Dorian's slide into crime and cruelty progresses, he stays magically youthful, while his beautiful portrait changes, revealing the hideous corruption of moral decay